Plasma Proteome Profiling of Ovarian Tumors: Comparative Analysis of Illumina SomaSeq Discovery and Olink Explore HT - Moskov, Mikaela; Enroth, Stefan; Borgmästars, Emmy (Uppsala University, 2026)
The plasma proteome from 85 individuals with ovarian tumors of benign (n = 23) or malignant (n=62) nature has been quantified using Illumina SomaSeq Discovery (SomaSeq), previously called Illumina Protein Prep (IPP), and Olink Explore HT (EHT). For 52 of these samples (9 benign and 43 malignant), there was also tumour tissue RNA data available.

The data attached to this repository consists of processed analysis results from the comparative analysis between the SomaSeq and EHT datasets. Supplementary Data 1 includes protein-protein correlations based on SomaSeq. Supplementary Data 2 includes the DESeq2 results from transcriptomic analysis for transcripts encoding for proteins in the SomaSeq and EHT panels. There is also an accompanied README describing the columns of the data.

Raw proteomic or transcriptomic data are not included.
Keywords: Proteomics and metabolomics; Medical and Health Sciences; Medicin och hälsovetenskap